COMPARATIVE STUDY OF ANALGESIC ALONG WITH TAPING TECHNIQUE VERSUS ANALGESIC ALONG WITH CRYOTHERAPY IN UNILATERAL PATELLO-FEMORAL OSTEOARTHRITIS OF KNEE JOINT - SOUMIK BASU; PROF.TUSHAR J PALEKAR; PROF.R.BALASARAVANAN; SOUMIK BASU (International Journal of Pharma and Bio Sciences, 2014)
Osteoarthritis(OA) is a leading cause of pain and disability in elder people world-wide. Cryotherapy has been proven to control pain in OA knee. Taping has shown relieving the pain.40 patients with unilateral patello femoral OA of knee joint of both the sexes were taken randomly, divided into Group A and Group B. Group A treated with Analgesic and taping Group B treated with Analgesic and Cryotherapy .Both the groups were treated daily for 15 days for 20-25 mins. Patients were evaluated with visual Analog Scale, Goniometer and Western Ontario and Mac Master- Universities Osteoarthritis index on day the1 and the day 15. The values are statistically analyzed to determine theireffect in reducing the pain and improving function. In comparison with VAS, ROM and WOMAC-pain, stiffness and difficulty scores, Group A shows significant improvement of all the parameters than Group B.